Por que é importante a identificação correta das espécies de haemonchus? - do Amarante, Alessandro Francisco Talamini [UNESP] (My University, 2011)
Parasitic gastroenteritis caused by Haemonchus spp. is a major cause of economic losses in the livestock industry because it impairs weight gain and increases mortality in cattle and small ruminants, especially in tropical and subtropical areas. The proper identification of the various species, as well as knowledge regarding the epidemiology of parasitic gastroenteritis, is essential for the establishment of sustainable strategies of parasite control. This review focuses on the use of easily applied, low-cost parasitological methods of identifying Haemonchus species on the basis of their morphology. In most studies carried out in Brazil, the distinctions between Haemonchus contortus and Haemonchus placei have not been considered. Many reports of H. contortus, particularly in cattle, might actually represent H. placei. The appropriate identification of species is therefore indispensable. In addition to the measurement of male spicules, new morphological characteristics, such as the synlophe, should be evaluated in order to differentiate between and among species. Measurements of infective larvae in fecal cultures can also indicate the identity of Haemonchus species. This approach can be quite useful in studies that do not involve animal sacrifice, such as studies of anthelmintic resistance based on the fecal egg count reduction test.
Why is it important to correctly identify haemonchus species?
Keywords: Haemonchus contortus; Haemonchus placei; Haemonchus similis; Morphology; Ruminants